Improved field emission by liquid elastomer modification of screen-printed CNT film morphology - Lee, H.; Lee, Y.; Cho, W.; Kim, J.; Lee, Y.; Hwang, S.; Ju, B. (2006)
The effect of improvement on the surface morphology of screen-printed carbon nanotube (CNT) films was studied by using the optically clear poly-dimethylsiloxane (PDMS) elastomer for surface treatment. After the PDMS activation treatment was applied to the diode-type CNT cathode, the entangled carbon nanotube (CNT) bundles were broken up into individual free standing nanotubes to remarkably improve the field-emission characteristics over the as-deposited CNT film. Also, the cathode film morphology of a top gated triode-type structure can be treated by using the proposed surface treatment technique, which is a low-cost process, simple process. The relative uniform emission image showed high brightness with a high anode current. This result shows the possibility of using this technique for surface treatment of large-size field emission displays (FEDs) in the future. ？ 2006 Taylor & Francis Group, LLC.